Kepribadian Guru BK dan Hubungannya dengan Minat Siawa Mengikuti Layanan Konseling Individual - Rahima Ayu; Nurhasanah Nurhasanah; Dahliana Dahliana (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
This research is entitled "BK Teacher's Personality and Its Relationship with Students' Interest in Following Individual Counseling Services in Banda Aceh State Middle School 17". This study aims to find out the description of the BK teacher's personality and the description of interest of students of Banda Aceh Middle School 17 to solve the problem through individual counseling services and the relationship between the two variables in class VIII students totaling 230 people. The sample is 146 students. This type of research is descriptive correlational with a quantitative approach and uses data collection techniques through questionnaires. The results of the descriptive analysis of the data show that the BK personality teacher's picture is in the high category. This can be seen from the large number of students in the high category, namely 114 people with a percentage of 78%. The description of students' interest in individual counseling services is at a high level. This is evidenced by the number of frequency of student answers as many as 82 people and a percentage of 56.2%. Based on the results of the study there is a relationship between the personality of the counselor with the students' interest in solving the problem through individual counseling services with a value of rcount rtable that is 0.684 0.1625 at alpha 0.05. That is, the personality of the BK teacher is positively and strongly related to students' interest in solving the problem through individual counseling services, so the Ha hypothesis is accepted. In other words, the higher or better the personality of the BK teacher, the higher the students' interest in solving the problem through individual counseling services Keywords: BK Teacher Personality, Student Interest,  Individual Counseling Service ABSTRAK Penelitian ini berjudul “Kepribadian Guru BK dan Hubungannya dengan Minat Siswa Mengikuti Layanan Konseling Individual pada SMP Negeri 17 Banda Aceh”.Penelitian ini bertujuan untuk mengetahui gambaran kepribadian guru BK dan gambaran minat siswa SMP Negeri 17 Banda Aceh menyelesaikan masalahnya melalui layanan konseling individual serta hubungan antara kedua variabel tersebut pada siswa kelas VIII yang berjumlah 230 orang. Adapun yang menjadi sampel yaitu 146 siswa.Jenis penelitian adalah deskriptif korelasional dengan pendekatan kuantitatif dan menggunakan teknik pengumpulan data melalui angket.Hasil analisis deskriptif data menunjukkan bahwa gambaran kepribadian guru BK berada pada kategori tinggi.Hal ini terlihat dari banyaknya jumlah siswa pada kategori tinggi yaitu 114 orang dengan persentase sebesar 78%.Gambaran minat siswa terhadap layanan konseling individual berada pada taraf tinggi.Hal itu dibuktikan dengan jumlah frekuensi jawaban siswa sebanyak 82 orang dan persentase sebesar 56,2%. Berdasarkan hasil penelitian terdapat hubungan antara kepribadian guru BK dengan minat siswa menyelesaikan masalahnya melalui layanan konseling individual dengan nilai rhitungrtabel yaitu 0,684 0,1625 pada alpha 0,05. Artinya, kepribadian guru BK berhubungan secara positif dan kuat dengan minat siswa menyelesaikan masalahnya melalui layanan konseling individual, sehingga hipotesis Ha diterima. Dengan kata lain, semakin tinggi atau baik kepribadian guru BK, maka semakin tinggi pula minat siswa menyelesaikan masalahnya melalui layanan konseling individual. Kata kunci:Kepribadian Guru BK, Minat Siswa, Layanan Konseling Individual